N-Acetyl Cysteine Mediates Protection from 2-Hydroxyethyl Methacrylate Induced Apoptosis via Nuclear Factor Kappa B–Dependent and Independent Pathways: Potential Involvement of JNK - Paranjpe, Avina (Oxford University Press, 2009)
The mechanisms by which resin based materials induce adverse effects in patients have not been completely elucidated. Here we show that 2-hydroxyethyl methacrylate (HEMA) induces apoptotic cell death in oral keratinocytes. Functional loss and cell death induced by HEMA was significantly inhibited in the presence of N-acetyl cysteine (NAC) treatment. NAC also prevented HEMA mediated decrease in vascular endothelial growth factor secretion. The protective effect of NAC was partly related to its ability to induce NF-κB in the cells, since HEMA mediated inhibition of nuclear NF-κB expression and function was significantly blocked in the presence of NAC treatment. Moreover, blocking of nuclear translocation of NF-κB in oral keratinocytes sensitized these cells to HEMA mediated apoptosis. In addition, since NAC was capable of rescuing close to 50% of NF-κB knockdown cells from HEMA mediated cell death, there is, therefore, an NF-κB independent pathway of protection from HEMA mediated cell death by NAC. NAC mediated prevention of HEMA induced cell death in NF-κB knockdown cells was correlated with a decreased induction of c-Jun N-terminal kinase (JNK) activity since NAC inhibited HEMA mediated increase in JNK levels. Furthermore, the addition of a pharmacologic JNK inhibitor to HEMA treated cells prevented cell death and restored NF-κB knockdown cell function significantly. Therefore, NAC protects oral keratinocytes from the toxic effects of HEMA through NF-κB dependent and independent pathways. Moreover, our data suggest the potential involvement of JNK pathway in NAC mediated protection.